(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The purpose of this work is to share the experience of the Department of Ukrainian Kryvyi Rih State Pedagogical University in the field of communication studies, in particular, in organizing the practical work of students at bachelor’s degree, master’s Degree and PhD Degree. The activity of the teachers of our department is aimed at ensuring that students and postgraduate students acquire communicative competences, which allow the modern teacher to get to a high level of realization of professional functions based on national and world standards. The focus of this work is an analysis of compliance of the State standards in speciality “Philology” and the content of the programs of disciplines of the department, which ensure the quality of higher education. In this context, the author talks about the three stages of communicative education. We draw attention to our own practical experience in teaching the course in Ukrainian Communology for PhD students. As a result, postgraduate students learn to predict the results of communication in different situations, to notice mistakes in communication, to submit information to avoid conflicts correctly. They acquire the skills to make informed decisions and to carry out their professional activities in accordance with national communication standards. The article also discusses the prospects for communication education in Ukraine, which today has not yet become a mandatory humanitarian component of vocational training.